Evaluation of Equality Education Program in PKMB Nurul Mubtadiin as a Nonformal Inclusion Institution - Supriatin (The Center for Disability Studies and Services Brawijaya University, 2018)
This study aims to describe the evaluation of the Package B PKBM Nurul Mubtadiin equality education program as a non-formal inclusion institution which covers the context of the evaluation of the Package B equality education program at PKBM Nurul Mubtadiin, evaluation of the input of Package B PKBM Nurul Mubtadiin's equality education program and evaluation of process implementation and the quality of the results of the Package B equality education program at PKBM Nurul Mubtadiin. This study uses a descriptive qualitative approach using the method of observation, interviews. One respondent was 1 blind student, 1 Tutor and PKBM Chairperson Nurul Mubtadin.